(untitled) (Window of Public Health Journal, 2025)
Unsafe actions are actions that violate or do not comply with safe work standards, so that they have the potential to cause work accidents. The purpose of this study was to see the relationship between training and unsafe actions in exploration workers at PT Riota Jaya Lestari, North Kolaka Regency. This type of research is quantitative research with a cross-sectional study approach. The sample of this study was conducted using a total sampling technique, totaling 70 workers. The instrument used was a questionnaire. Data analysis was carried out univariately and bivariately using the chi-square test of the SPSS application. The results of this study indicate that training obtained a p-value = 0.000 <0.05, which means there is a relationship between training and unsafe actions in exploration workers. These findings highlight the importance of training, which can empower workers and improve safety culture. Based on the results obtained, the researcher suggests that workers participate in training conducted by the company more often so that they gain knowledge about occupational safety and health (K3) to avoid unsafe actions in the workplace.